The Effect of Instagram Content Quality of HL Outfit on Consumer Purchase Intention through Brand Image as a Mediating Variable - Dewi Candrawati; Egan Evanzha Yudha Amriel (Indonesian Journal Economic Review (IJER), 2026)
The rapid growth of digital marketing has made Instagram one of the most dominant channels for fashion brands to communicate with consumers, yet a large follower base does not automatically translate into a high engagement rate or purchase intention. This phenomenon is evident in the Instagram account of HL Outfit, a local Indonesian fashion brand with 292,000 followers whose engagement rate remains below the ideal standard despite consistent content uploads. While prior studies have largely examined the direct effect of social media content on purchase decisions, comparatively little attention has been paid to how brand image translates content quality into purchase intention for local fashion brands — a gap this study addresses. This study aims to examine the effect of Instagram content quality on consumer purchase intention, both directly and indirectly through brand image as a mediating variable. A quantitative approach was employed using Partial Least Square Structural Equation Modeling (PLS-SEM) with SmartPLS 3. Data were collected from 100 respondents selected through purposive sampling, consisting of personal Instagram account users who actively follow the HL Outfit account, using a five-point Likert-scale questionnaire distributed via Google Form. The results show that content quality has a positive and significant effect on purchase intention (β = 0.219; t = 3.017; p = 0.003) and on brand image (β = 0.498; t = 2.982; p = 0.003); brand image has a positive and significant effect on purchase intention (β = 0.444; t = 3.798; p = 0.000); and brand image partially mediates the effect of content quality on purchase intention (β = 0.221; t = 2.131; p = 0.034). The model explains 24.8% of the variance in brand image and 34.2% of the variance in purchase intention, indicating a weak-to-moderate predictive capability. These findings suggest that local fashion brands should pursue a two-track digital-marketing strategy: enhancing the informativeness, relevance, visual appeal, and interactivity of Instagram content, while deliberately curating brand-image cues — such as consistent visual identity and authentic product storytelling — since brand image functions as the primary conduit that converts content quality into purchase intention.